Estimation of debris flight trajectories of roof cover from low-rise buildings - Mejorin, Angela; Kopp, Gregory A. (Frontiers in Built Environment, 2024)
During windstorm events buildings can represent both wind-borne debris source and target elements. Roof cover can fail and be blown away, impacting the surrounding construction, reaching significant distances. Analytical models to calculate debris trajectories generally consider the flight to occur in uniform flow. These models are, therefore, not considering source building aerodynamics, yielding results that can be significantly overestimated. This paper defines Udebris, the equivalent uniform wind speed that leads to the analytical solutions in roof cover flight assessment that matches the available datasets that considers source building aerodynamics. To calculate Udebris, the concept of response time is introduced: t* is a parameter that physically captures the tendency of debris elements to fly with the wind gust. The identification of these times, typical for each roof cover type, leads to a selection of a gust factor, G, to account for the debris response. Roof/wake factors (FR) are also used for Udebris calculation, based on roof cover type, locations on the roof, neighborhood settings. These last factors are estimated based on t*, on the boundary layer that develops on the source building roof slope, and on considerations about turbulence effects. A Monte Carlo simulation-based approach for estimating roof cover element flight trajectories is, therefore, presented and validated against experimental datasets. The results indicate alignment with experimental observations, underscoring the potential utility of this approach for dealing with wind-borne debris issues in disaster preparedness, building technology, and structural design.